The effectiveness of baby massage in increasing baby weight - Cahya, Sara Eka; Rokhanawati, Dewi (Journal of Health Technology Assessment in Midwifery, 2024)
Babies born with low birth weight (LBW) are more vulnerable to health issues and are a leading cause of neonatal death. Globally, cases of low birth weight in the world reach 15.5%, with 90% of them occurring in developing countries. The aim of the review was to identify evidence regarding the effectiveness of baby massage in increasing baby weight. This Scoping Review was referring to the steps taken by Arksey and O'maley, the articles included published from 2018 to 2023, in English and Indonesian and focus on baby weight gain, in the The data source from journals were accessed via the Pubmed, Wiley, and Google Scholar databases. 103 journals were filtered, 96 journals were excluded, 7 articles were taken based on title and abstract, 7 journals were assessed for eligibility, 2 were excluded because they did not meet the inclusion and exclusion criteria, the journal was included in the review 5 who meet the requirements. This research carried out Critical Appraisal according to the design in the research journal, namely Critichal Appraisal Randomized Control Trial and Critichal Appraisal Quasi Experiment. A scoping review of 5 journals regarding the effectiveness of baby massage in increasing baby weight identified the main research theme, namely giving massage to babies, factors that influence baby massage and obstacles to carrying out baby massage. Based on the results of the four journals it can be concluded that baby massage is effective. in baby weight gain.